AB0694 Resolution of Generalized Deep Variant Morphea (Morphea Profunda): A Case Series of Three Patients Successfully Treated with Abatacept. (9th June 2015) - Adeeb, F.; Anjum, S.; Hussein, O.; Ng, W.L.; Brady, M.; Morrissey, S.; Devlin, J.; Fraser, A.D.
Abstract : Background: Deep Variant Morphea (DMV), previously known as morphea profunda, is an exceptionally rare form of sclerosis that is confined to the skin, and unlike scleroderma, has no systemic or internal organ involvement. The inflammation and sclerosis involves layers of the deep dermis, panniculus, fascia or even the underlying superficial muscle. An initial inflammatory phase, which can be extremely painful, is followed by skin sclerosis, which may cause joint contractures. It is a progressive and highly destructive disease, with apparently no effective treatment, leaving patients with hard, rock-like skin, and ultimately in the worst cases, early death. Objectives: To evaluate the treatment impact and efficacy of Abatacept (Orencia) in patients presented with Deep Variant Morphea. Methods: Three patients with established deep variant morphea and no contraindications to Abatacept were included in this prospective, open label study. Skin biopsies were performed to confirm deposition of dense fibrous tissue in the appropriate layer of the skin. Baseline Modified Rodnan Score were performed independently by 3 clinicians. VAS scores (10cm) were measured at baseline for Patient Global Disease Activity (PGDA), Patient Global Pain (PGP), Patient Day Pain (PDP), Patient Night Pain (PNP), Physician Global Disease Activity (PhGDA). Further investigations include High Resolution Ultrasound (HRUS) at 10 sites as well as whole body MRI.Patients were commenced on Abatacept (Orencia) as per body weight (10mg/kg), intravenously with tapering dose of oral prednisolone. All outcome measures including imaging were repeated 6-months after commencement of therapy to monitor disease progression. Results: All patients tolerated the Abatacept well and showed dramatic improvement including their Baseline Rodnan Score, VAS outcome measures and imaging. All of them continued to be in complete clinical remission. Conclusions: Deep variant morphea are difficult to treat. Therefore, timely diagnosis of the condition is crucial, as treatment should be aimed during the early inflammatory phase. The three cases further offer support for the use of Abatacept in cases of acute deep variant morphea, a dreadful, disfiguring and life-threatening disease with apparently no effective treatment until now. References: Zwischenberger BA, Jacobe HT. A systematic review of morphea treatments and therapeutic algorithm. J Am Acad Dermatol 2011: 65: 925–941. Fett N, Werth VP. Update on morphea: part II. Outcome measures and treatment. J Am Acad Dermatol 2011: 64: 231–242; quiz 43–44. B. Stausbol-Gron et al. Abatacept is a Promising Treatment for Patients with Disseminated Morphea Profunda: Presentation of Two Cases. Acta Derm Venereol 2011; 91: 686-688. Disclosure of Interest: None declared